2021
DOI: 10.3390/ma14030682
|View full text |Cite
|
Sign up to set email alerts
|

Machine Vision for As-Built Modeling of Complex Draped Composite Structures

Abstract: The transition in the use of fiber composite structures from special applications to application in the mass market is accompanied by high demands in quality assurance. The consequential costs of unclear process design, unknown fiber orientations, and uncertainty regarding the effects of any fiber angle deviations can lead to market considerations (higher costs/time for development) in mass production that advise against the use of fiber composites, despite their superiority compared with conservative material… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 47 publications
(49 reference statements)
0
4
0
Order By: Relevance
“…Stationary cameras were used on these steady production processes where no geometrical information was required. The obtained values were used for quality assessment (Lian et al, 2000) and process control (Mersmann, 2011;Lekanidis and Vosniakos, 2020), simple damage detection (Wilhelmsen and Ostrom, 2016), and for importing material relevant input data (fiber orientation) into a virtual environment finite element analysis (FEA) models for further use in numerical simulation (Stender et al, 2019;Döbrich et al, 2021). Studies on using composite machine vision in material research to study the fatigue behavior of glass-fiber-reinforced composites are also found in the literature (Song et al, 2022).…”
Section: State Of the Artmentioning
confidence: 99%
See 2 more Smart Citations
“…Stationary cameras were used on these steady production processes where no geometrical information was required. The obtained values were used for quality assessment (Lian et al, 2000) and process control (Mersmann, 2011;Lekanidis and Vosniakos, 2020), simple damage detection (Wilhelmsen and Ostrom, 2016), and for importing material relevant input data (fiber orientation) into a virtual environment finite element analysis (FEA) models for further use in numerical simulation (Stender et al, 2019;Döbrich et al, 2021). Studies on using composite machine vision in material research to study the fatigue behavior of glass-fiber-reinforced composites are also found in the literature (Song et al, 2022).…”
Section: State Of the Artmentioning
confidence: 99%
“…The field of view for those applications is rather small and is limited to a specific section of composite parts or composite production processes. The digital image evaluation at the component level of composite structures is carried out by handguided or robot-guided camera systems (Kunze et al, 2020;Döbrich et al, 2021). Commercially available systems are provided by Hexagon (Sweden, formerly Apodius) [hand-guided inspection system (Stender et al, 2019;Antoniou et al, 2020;Döbrich et al, 2021)] or CIKONI (Germany) [robot-guided Hexagon system (Pasco et al, 2019)].…”
Section: State Of the Artmentioning
confidence: 99%
See 1 more Smart Citation
“…This system generates an STL file that can be compared to the as-planned (undeformed) geometry via manual overlay so that the maximum deviation between the geometries can be minimized. The global comparison was done similar to previous studies [ 20 ] using MeshLab and the built-in Hausdorff distance. The obtained result was then scaled to the measured maximum distance based on a comparison of the as-planned geometry and the STL file obtained from scanning.…”
Section: Implementation and Application On A Structural Levelmentioning
confidence: 99%